Battery cell coating film, preparation method thereof, battery cell and battery

By using porphyrin-based compounds to graft the coating film formed by mixing silicon particles with polymer on the battery cell, the transition metal ions are adsorbed, and the problem that the existing battery cell coating materials cannot improve the battery cycle performance is solved, and the battery cell is realized Highly efficient adsorption and electrochemical performance improvement.

CN119231040APending Publication Date: 2024-12-31GAC AION NEW ENERGY AUTOMOBILE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411495004.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing battery cell cladding materials cannot improve the electrochemical performance of the battery, especially the cyclic performance. They can only serve as insulation and buffering, and cannot effectively adsorb the transition metal ions released by the positive electrode active material during the charging and discharging process, resulting in the negative electrode sheet. Structure and performance are damaged.

Method used

The battery core coating film consisting of porphyrin-based compounds grafted silicon particles is used to form a battery core coating film by mixing it with the polymer, adsorbing transition metal ions, reducing the amount of deposited on the surface of the negative electrode sheet, thereby increasing the circulation of the battery core. performance.

Benefits of technology

While maintaining the insulation and buffering functions, it effectively adsorbs transition metal ions, improves the cycling performance of the battery, extends the service life of the battery and improves the electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119231040A_ABST
    Figure CN119231040A_ABST
Patent Text Reader

Abstract

The invention provides a battery cell coating film and a preparation method thereof, a battery cell and a battery, and belongs to the technical field of battery preparation. The cell coating film comprises porphyrin compound grafted silicon particles and a polymer. The porphyrin compound grafted silicon particles are introduced into the battery cell coating film, so that the cycle performance of the corresponding battery cell can be effectively improved while the insulation and buffer functions are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery preparation, and in particular to a battery cell coating film and a preparation method thereof, a battery cell and a battery. Background Art

[0002] The cell coating material of existing power batteries is usually Mylar film, which mainly plays an insulating role, isolating the contact between the pole piece and the metal aluminum shell to prevent the battery from short circuiting. At the same time, the cell coating material can also play a buffering role, reducing the vibration damage of the cell when it is on the vehicle. However, other than this, the existing cell coating material cannot improve the electrochemical performance of the battery (such as cycle performance). Summary of the invention

[0003] To solve the above problems, the purpose of the embodiments of the present application includes providing a battery cell coating film and a preparation method thereof, a battery cell and a battery. By providing a battery cell coating film including porphyrin compound grafted silicon particles, it is possible to improve the cycle performance of the corresponding battery cell while exerting the insulation and buffering functions of the battery cell coating material.

[0004] In a first aspect, the present application provides a battery core coating film, comprising porphyrin compound grafted silicon particles and a polymer.

[0005] In the above technical solution, a battery cell coating film is used instead of the conventional Mylar film. Since the battery cell coating film contains porphyrin compound grafted silicon particles, it can not only play the conventional functions of insulation and buffering, but also adsorb transition metal ions (such as ions corresponding to Fe, Co, Ni and Mn) released by the positive electrode active material during the charge and discharge cycle, thereby reducing the amount of transition metal ions that reach the negative electrode sheet through the diaphragm and deposit on the negative electrode surface, reducing the influence of transition metal ion deposition on the structure and performance of the negative electrode sheet, and thereby improving the cycle performance of the corresponding battery cell.

[0006] In some embodiments of the present application, the thickness of the battery cell coating film is 1 nm to 1 mm.

[0007] In the above technical solution, the thickness of the battery cell coating film can be adjusted according to the actual application, so as to reduce the impact on the battery energy density while ensuring the insulation and buffering performance, and be able to fully absorb transition metal ions to improve the battery's cycle performance.

[0008] In some embodiments of the present application, the mass ratio of the porphyrin compound grafted silicon particles to the polymer is (1-99):(0-99).

[0009] Optionally, the polymer includes at least one of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), polytetrafluoroethylene, polyhexafluoropropylene, polyacrylate, polymethacrylate, polyacrylamide, polymethacrylamide, epoxy resin, polyvinyl pyrrolidone, carboxymethyl cellulose, sodium carboxymethyl cellulose, cellulose or chitosan.

[0010] In the above technical solution, the mass proportion and types of polymers can be implemented in a wide range, which is convenient for making corresponding adjustments according to the actual application system, thereby improving the system compatibility of the battery cell coating film during application.

[0011] In some embodiments of the present application, the battery core coating film further includes an inorganic oxide, and the mass ratio of the porphyrin compound grafted silicon particles to the inorganic oxide is (1-99):(0-99).

[0012] Optionally, the inorganic oxide includes at least one of boehmite, alumina, silica, titania, ferric oxide or ferrous oxide.

[0013] In the above technical solution, by adding inorganic oxides to the battery cell coating film, the processing convenience can be improved, the production cost can be reduced, and the mechanical properties of the battery cell coating film can be improved.

[0014] In some embodiments of the present application, the battery cell coating film includes a functional layer and a polymer base film, the functional layer includes porphyrin compound grafted silicon particles and a polymer, and the functional layer is located on at least one side surface of the polymer base film.

[0015] Optionally, the polymer base film has a thickness of 1 nm to 100 μm;

[0016] Optionally, the material of the polymer base film includes at least one of polyethylene terephthalate, polyvinyl alcohol, polyethylene, polypropylene, polyacrylonitrile, polyimide or polyetherimide.

[0017] In the above technical solution, adding a polymer base film can further enhance the overall strength and structural stability of the battery cell coating film, thereby better playing the role of insulation and buffering.

[0018] In a second aspect, the present application provides a method for preparing the above-mentioned battery core coating film, comprising the following steps:

[0019] S1: dissolving a porphyrin compound having an alkenyl group in a solvent and mixing the mixture with mercapto-functionalized silicon particles, and performing a grafting reaction under ultraviolet light to prepare porphyrin compound grafted silicon particles;

[0020] S2: Mix the porphyrin compound grafted silicon particles and the polymer, and form a battery core coating film after curing.

[0021] In the above technical scheme, porphyrin compounds with alkenyl groups and mercapto-functionalized silicon particles are selected as raw materials. The alkenyl groups and mercapto groups can be directly reacted and grafted under ultraviolet light. The preparation method is simple, the grafting rate is high, and there are few by-products and the product purity is high. The prepared porphyrin compound grafted silicon particles are not easy to react chemically in the battery system, the chemical bonds are not easy to break, and have excellent stability. The porphyrin compound grafted silicon particles and the polymer are mixed, and the battery cell coating film can be simply prepared by spinning or coating.

[0022] In some embodiments of the present application, step S2 includes: mixing porphyrin compound grafted silicon particles and polymer to form a slurry, coating or spinning the slurry on at least one surface of a polymer base film, and curing it on the surface of the polymer base film to form a functional layer to obtain a battery cell coating film.

[0023] In the above technical scheme, the functional layer can be prepared by a variety of methods, which is applicable to both the coating structure prepared by a coating process and the spinning structure prepared by a spinning process, so as to facilitate flexible adjustment according to actual applications, thereby facilitating the promotion and application of the battery cell of the present application.

[0024] In some embodiments of the present application, the mercapto functionalized silicon particles are 3-mercaptopropyl grafted silicon particles. The porphyrin compound having an alkenyl group includes at least one of protoporphyrin, protoporphyrin monomethyl ester, protoporphyrin dimethyl ester, protoporphyrin monosodium salt, protoporphyrin disodium salt, protoporphyrin monolithium salt or protoporphyrin dilithium salt.

[0025] In the above technical solution, specific mercapto-functionalized silicon particles and porphyrin compounds are selected, and the raw materials are simple and easy to obtain, which can improve the reaction efficiency and reduce the production cost.

[0026] In some embodiments of the present application, the grafting reaction temperature is 40 to 80° C., and the time is 6 to 24 hours.

[0027] Optionally, the solvent is methanol.

[0028] Optionally, after the grafting reaction, the method further comprises: filtering and washing with methanol, and vacuum drying at 60-100°C.

[0029] In the above technical solution, by controlling the conditions of the grafting reaction, the grafting stability and grafting rate can be enhanced and the purity of the product can be ensured.

[0030] In a third aspect, the present application provides a battery cell, comprising a battery cell body and the above-mentioned battery cell coating film, the battery cell body comprising a positive electrode sheet, a negative electrode sheet and a separator, the separator is located between the positive electrode sheet and the negative electrode sheet, and the battery cell coating film is coated on the outside of the battery cell body.

[0031] In the above technical solution, since the battery cell coating film includes porphyrin compound grafted silicon particles, when it is arranged outside the battery cell body, it can replace the traditional Mylar film, and effectively improve the cycle performance of the battery cell while playing the insulation and buffering functions.

[0032] In a fourth aspect, an embodiment of the present application provides a battery, comprising a shell, an electrolyte and the above-mentioned battery cell, the battery cell and the electrolyte are contained in the shell, the electrolyte infiltrates the positive electrode sheet, the negative electrode sheet and the separator, and the battery cell coating film is used to insulate the battery cell body from the shell.

[0033] In the above technical solution, by providing a battery cell coating film with specific components, the safety performance of the battery can be ensured while improving the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 A schematic diagram of the side structure of a battery cell provided in an embodiment of the present application;

[0036] Figure 2 A schematic diagram of the cross-sectional structure of a battery cell provided in an embodiment of the present application;

[0037] Figure 3 A schematic cross-sectional structure diagram of another battery cell provided in an embodiment of the present application;

[0038] Figure 4 A schematic cross-sectional structure diagram of another battery cell provided in an embodiment of the present application;

[0039] Figure 5 A schematic cross-sectional view of a battery cell coating film provided in an embodiment of the present application;

[0040] Figure 6 for Figure 5 An enlarged schematic diagram of the surface of the battery cell coating film is shown;

[0041] Figure 7 A schematic cross-sectional view of another battery cell coating film provided in an embodiment of the present application;

[0042] Figure 8 for Figure 7 An enlarged schematic diagram of the surface of the battery cell coating film is shown;

[0043] Fig. 9A schematic cross-sectional view of another battery cell coating film provided in an embodiment of the present application;

[0044] Fig.10 for Fig. 9 An enlarged schematic diagram of the surface of the battery cell coating is shown.

[0045] Description of reference numerals:

[0046] 100-battery cell; 10-battery cell body; 20-battery cell coating film; 21-functional layer; 22-polymer base film. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0048] During the charge and discharge process of lithium-ion batteries, the continuous deintercalation of lithium ions causes structural distortion. The transition metal ions in the positive electrode active material will slowly dissolve into the electrolyte and migrate to the negative electrode surface through the diaphragm to deposit, causing the negative electrode SEI film to be destroyed and thus causing the electrochemical performance of the battery to decline. In response to this technical problem, current research usually adopts methods such as adding metal chelating agents to the positive electrode or diaphragm, but no improvement has been made to the structure or composition of the battery cell coating material. In addition, the current battery cell coating material is usually Mylar film, which only plays an insulating and buffering role, has a relatively simple function, and cannot improve the electrochemical performance of the battery (such as cycle performance).

[0049] Based on this, the researchers of this application have creatively discovered that: functionalized silicon particles are grafted with porphyrin compounds to obtain porphyrin compound grafted silicon particles, which are prepared into battery cell coating materials and coated on the surface of the battery cell. This can not only play the conventional functions of insulation and buffering, but also adsorb transition metal ions (such as ions corresponding to Fe, Co, Ni and Mn) released by the positive electrode active material in the positive electrode during the charge and discharge cycle, thereby reducing the amount of transition metal ions that reach the negative electrode through the diaphragm and deposit on the surface of the negative electrode sheet (transition metal ion deposition will cause the function of the negative electrode of the battery cell to be affected or even damaged), thereby improving the cycle performance of the battery cell, so as to be able to improve the cycle performance of the corresponding battery cell while playing the insulation and buffering functions of the battery cell coating film.

[0050] In the following, a battery cell coating film and a preparation method thereof, a battery cell and a battery including the battery cell according to an embodiment of the present application are described in detail.

[0051] Figure 1A schematic diagram of the side structure of a battery cell provided in this application, Figure 2 This is a schematic diagram of the cross-sectional structure of a battery cell provided in one embodiment of the present application. Figure 1 and Figure 2 The battery cell 100 includes a battery cell body 10 and a battery cell coating film 20 coated on the outside of the battery cell body 10. The battery cell body 10 includes a positive electrode sheet, a negative electrode sheet and a separator, the separator is located between the positive electrode sheet and the negative electrode sheet, and the battery cell coating film 20 includes porphyrin compound grafted silicon particles and polymers.

[0052] It should be noted that the various structural units in the battery cell 100 are not specifically limited and can be arranged according to conventional selections in the art. The positive electrode sheet, separator and negative electrode sheet in the battery cell 100 can be stacked in sequence to form a laminated structure or can be wound to form a wound structure.

[0053] It can be understood that the positive electrode sheet in the battery cell 100 includes a positive electrode current collector and a positive electrode active material located on the surface of the positive current collector. During the battery cycle, the transition metal ions (such as ions corresponding to Fe, Co, Ni and Mn) in the positive electrode active material will inevitably dissolve into the electrolyte and migrate to the surface of the negative electrode sheet through the diaphragm, destroying the structure of the negative electrode sheet. In the embodiment of the present application, the positive electrode sheet, the negative electrode sheet and the diaphragm can all be conventionally selected, which is not limited here, and can be set according to the conventional selection in the field. Taking lithium-ion batteries as an example, the positive electrode active material can be LiMPO4 or LiNO2, wherein M can be at least one of Fe, Co, Ni, and Mn, and N can be at least one of Ni, Co, Mn, and Al. As an example, the positive electrode active material can be lithium iron phosphate (referred to as LFP), lithium manganese iron phosphate (referred to as LMFP), lithium manganese oxide (referred to as LMO), lithium cobalt oxide (referred to as LCO), lithium nickel manganese oxide (referred to as LNMO), lithium nickel cobalt manganese oxide (referred to as NCM), and lithium nickel cobalt aluminum oxide (referred to as NCA). The particle size of the positive electrode active material is 10nm to 100μm. The positive electrode current collector can be aluminum foil or carbon-coated aluminum foil. The negative electrode sheet includes a negative electrode current collector and a negative electrode active material located on the surface of the negative electrode current collector, the negative electrode active material can be copper foil, and the negative electrode active material can be graphite. The separator can be a polyethylene separator, etc.

[0054] It should be noted that the cell coating film 20 is disposed on the surface of the cell body 10. The thickness of the cell coating film 20 may be 1 nm to 1 mm, for example, 0.01 mm, 0.1 mm, 1 mm, etc.

[0055] The method for preparing the battery core coating film 20 may include the following steps:

[0056] S1: dissolving a porphyrin compound having an alkenyl group in a solvent and mixing the mixture with mercapto-functionalized silicon particles, and performing a grafting reaction under ultraviolet light to prepare porphyrin compound grafted silicon particles.

[0057] It should be noted that grafting porphyrin compounds onto silicon particles refers to grafting porphyrin compounds onto the surface of silicon particles, wherein the porphyrin compounds may include porphyrin, protoporphyrin or porphyrin derivatives.

[0058] The porphyrin compound having an alkenyl group may be at least one of protoporphyrin, protoporphyrin monomethyl ester, protoporphyrin dimethyl ester, protoporphyrin monosodium salt, protoporphyrin disodium salt, protoporphyrin monolithium salt or protoporphyrin dilithium salt. The mercapto-functionalized silicon particles may be 3-mercaptopropyl grafted silicon particles.

[0059] The diameter of the thiol-functionalized silicon particles may be 0.1 nm to 1 μm, and the thiol loading may be 0.1 mmol / g to 10 mmol / g. As an example, the diameter of the thiol-functionalized silicon particles may be 100 nm, and the thiol loading may be 0.3 mmol / g.

[0060] By controlling the diameter of the mercapto-functionalized silicon particles, the particle size of the porphyrin compound grafted silicon particles can be adjusted accordingly. In addition, by controlling the mercapto loading amount, the porphyrin compound can fully react with the olefinic group in the porphyrin compound.

[0061] In the grafting reaction, the molar ratio of the alkenyl group in the porphyrin compound with alkenyl group and the mercapto group in the mercapto functionalized silicon particles can be controlled to be about (1-20): 1. By controlling the excess of the porphyrin compound, the grafting rate after the reaction can reach 100%.

[0062] The conditions of the grafting reaction include: the grafting reaction temperature is 40-80°C, the time is 6-24 hours. The solvent can be methanol, preferably anhydrous methanol. After the grafting reaction, the following steps are further performed: filtering and washing with methanol, and vacuum drying at 60-100°C.

[0063] As an example, the general structural formula of porphyrin compound grafted silicon particles is shown in formula (I):

[0064]

[0065] Among them, R3, R5, R7, R8, R 10 , R 12 , R 13 , R 15 , R 17 , R 18 , R 20 are each independently phenyl, vinyl, allyl, C n H 2n+1 , C n H 2nOH, C n H 2n CHO, C n H 2n COOH, C n H 2n COONa、C n H 2n COOLi, C n H 2n COOC n H 2n , C n H 2n SH, n is an integer between 0 and 20; i and j are each independently an integer between 0 and 10.

[0066] As an example, the grafting reaction process of protoporphyrin IX and 3-mercaptopropyl grafted silicon particles is shown in the following formula:

[0067]

[0068] S2: Mix the porphyrin compound grafted silicon particles and the polymer, and form a battery core coating film after curing.

[0069] In some embodiments, the battery cell coating film 20 may further include inorganic oxides and / or polymers, and the mass ratio of porphyrin compound grafted silicon particles, inorganic oxides and polymers may be (1-99):(0-99):(0-99).

[0070] Wherein, the inorganic oxide can be selected from at least one of boehmite, alumina, silicon dioxide, titanium dioxide, ferric oxide or ferric oxide. The polymer can be selected from at least one of polyvinylidene fluoride, poly (vinylidene fluoride-hexafluoropropylene), polytetrafluoroethylene, polyhexafluoropropylene, polyacrylate, polymethacrylate, polyacrylamide, polymethacrylamide, epoxy resin, polyvinyl pyrrolidone, carboxymethyl cellulose, sodium carboxymethyl cellulose, cellulose, chitosan, polyethylene terephthalate, polyvinyl alcohol, polyethylene, polypropylene, polyacrylonitrile, polyimide and polyetherimide. The molecular weight of the polymer can be 1000 to 3 million.

[0071] In step S2, the curing film can be formed by spinning or coating. The battery core coating film 20 can be formed into an integrated structure by spinning or coating, and then wrapped on the surface of the battery core body 10 to obtain the battery core 100. Specifically, melt spinning, electrostatic spinning or coating can be used.

[0072] See also Figure 2When the battery body 10 only includes a layer of battery coating film 20, that is, the battery coating film 20 is a whole, step S2 may include the step of mixing the porphyrin compound grafted silicon particles and the polymer and spinning them into a film to obtain the battery coating film. At this time, the thickness of the battery coating film 20 may be 0.1 mm. Figure 5 is a cross-sectional schematic diagram corresponding to the battery core coating film 20, Figure 6 It is a schematic diagram of an enlarged surface of the corresponding battery core coating film 20 .

[0073] See also Figure 3 and Figure 4 The battery core coating film 20 includes a functional layer 21 and a polymer base film 22 . The functional layer 21 includes porphyrin compound grafted silicon particles and a polymer. The functional layer 21 is located on at least one side surface of the polymer base film 22 .

[0074] The polymer base film 22 may have a thickness of 1 nm to 100 μm, and the material of the polymer base film 22 includes at least one of polyethylene terephthalate, polyvinyl alcohol, polyethylene, polypropylene, polyacrylonitrile, polyimide or polyetherimide. As an example, the polymer base film 22 may have a thickness of 0.1 mm.

[0075] As an example, step S2 may include the steps of: dispersing porphyrin compound grafted silicon particles and polymer in a solvent to obtain a slurry, and then spraying the slurry onto the surface of the polymer base film 22 through a coating process to form a functional layer 21 to obtain a battery cell coating film 20. For a cross-sectional schematic diagram of the battery cell coating film obtained by the preparation method, please refer to Figure 7 , please refer to the corresponding surface enlargement diagram Figure 8 .

[0076] As another example, step S2 may include the steps of: dispersing porphyrin compound grafted silicon particles and polymer in a solvent to obtain a slurry, and then spinning the slurry on the surface of the polymer base film 22 to form a functional layer 21 to obtain a battery cell coating film 20. For a schematic diagram of the battery cell coating film obtained by the preparation method, please refer to Fig. 9 , please refer to the corresponding surface enlargement diagram Fig.10 .

[0077] It should be noted that the form of the spinning process is not limited, and may include, for example, melt spinning or electrospinning.

[0078] It should be noted that since coating and spinning both adopt common and well-known preparation methods in the art, they can be set according to the conventional selection in the art during specific implementation, and will not be elaborated in detail here.

[0079] An embodiment of the present application also provides a battery, including a shell, an electrolyte and the above-mentioned battery cell, the battery cell and the electrolyte are contained in the shell, the electrolyte infiltrates the positive electrode sheet, the negative electrode sheet and the separator, and the battery cell coating film is used to insulate and connect the battery cell body to the shell.

[0080] It should be noted that in the embodiments of the present application, the battery may be a lithium-ion battery, a lithium-sulfur battery, a sodium-ion battery, etc., but is not limited to this.

[0081] The features and performance of the present application are further described in detail below in conjunction with specific embodiments.

[0082] The porphyrin compound-grafted silicon particles used in the examples were prepared by the following preparation method:

[0083] Take 100g silicon particles (particle diameter is 100nm) and slowly add them to 1L of Piranha solution under magnetic stirring, stir at 90℃ for 1h, filter and wash with a large amount of pure water, and complete activation by vacuum drying at 60℃. Take the above activated silicon particles, then add 600mL of 60mmol / L toluene solution of 3-mercaptopropyltrimethoxysilane, stir and react for 12h, filter and wash with acetone and pure water, and vacuum dry at 120℃ to obtain 3-mercaptopropyl grafted silicon particles with a mercapto loading of 0.3mmol / g.

[0084] 134.9 g of protoporphyrin IX (Aladdin, CAS: 553-12-8) was dissolved in 1214.1 g of anhydrous methanol, and then 100 g of the above 3-mercaptopropyl grafted silicon particles were added, stirred and dispersed at 60°C, and irradiated with ultraviolet light for 12 hours. Afterwards, it was filtered and washed with 12000 g of anhydrous methanol, and then vacuum dried at 80°C to obtain protoporphyrin IX grafted silicon particles (Pr / Si for short).

[0085] Example 1

[0086] The present application provides a battery B1. The battery cell of the battery B1 includes a battery cell body and a layer of battery cell coating film coated outside the battery cell body. The preparation method thereof includes the following steps:

[0087] (1) Preparation of battery cell coating materials

[0088] Take 80g of polyethylene terephthalate (PET, weight-average molecular weight of 100,000) and 20g of protoporphyrin IX grafted silicon particles, mix them at room temperature for 12h, then make a film by melt spinning at 260°C, and then hot press at 250°C for 1h to obtain a film with a thickness of 0.1mm, and cut the film into the size of the battery cell for use.

[0089] (2) Preparation of positive electrode

[0090] Take 96g of lithium nickel manganese oxide (LNMO, chemical formula LiNi 0.5 Mn 1.5 O4), 1.8g polyvinylidene fluoride, and 2.2g conductive carbon were dispersed at high speed for 8 hours and then coated on both sides of an aluminum foil with a thickness of 12μm, then dried at 100℃ and cut into positive electrode sheets for use.

[0091] (3) Preparation of negative electrode sheet

[0092] Take 95.6g of artificial graphite, 1.5g of carboxymethyl cellulose, 1.1g of conductive carbon, and 4.5g of styrene-butadiene rubber latex (solid content 40wt%), disperse them at high speed for 8h, then coat them on both sides of a copper foil with a thickness of 8μm, then dry them at 100℃, and cut them into negative electrode sheets for use.

[0093] (4) Preparation of batteries

[0094] The positive electrode sheet, negative electrode sheet and polyethylene separator with a thickness of 14 μm are taken as above and made into a battery body through a lamination process, and then the battery body is coated with the battery coating material prepared in step (1) to finally make an aluminum shell battery, followed by normal liquid injection, formation and capacity separation to obtain battery B1.

[0095] Example 2

[0096] The present embodiment provides a battery B2. The battery cell of the battery B2 includes a battery cell body and a layer of battery cell coating film coated on the battery cell body. The preparation method thereof is different from that of the embodiment 1 only in that:

[0097] In step (1), the raw material of the battery core coating material also includes silicon dioxide, and the specific steps include:

[0098] Take 80g of polyethylene terephthalate (weight average molecular weight of 100,000), 10g of protoporphyrin IX grafted silicon particles and 10g of silica, mix them at room temperature for 12h, then make a film by melt spinning at 260℃, and then hot press at 250℃ for 1h to obtain a film with a thickness of 0.1mm, and cut the film into the size of the battery cell for use.

[0099] Example 3

[0100] The present embodiment provides a battery B3, wherein the battery cell of the battery B3 includes a stacked battery cell coating film and a polymer base film, and the preparation method thereof is different from that of the embodiment 1 only in that:

[0101] In step (1), the film-forming method of the cell coating material is different, and the specific steps include:

[0102] Take 80g of polyvinylidene fluoride (PVDF, weight average molecular weight 600,000), dissolve it in 720g of N-methylpyrrolidone (NMP), then add 20g of protoporphyrin IX grafted silicon particles, disperse at high speed for 5h, and obtain slurry. Use electrostatic spinning method, use PET film with a thickness of 0.1mm as the polymer base film, spin the slurry on one surface of the PET film, dry it at 100℃ and then hot press it to obtain a film with a thickness of 0.11mm, and cut the film into the size of the battery cell for use.

[0103] Example 4

[0104] The present application embodiment provides a battery B4, wherein the battery cell of the battery B4 comprises a battery cell coating film, a polymer base film and a battery cell coating film stacked in sequence, and the preparation method thereof is different from that of the embodiment 3 only in that:

[0105] The slurry was spun on two opposite surfaces of the PET film.

[0106] Example 5

[0107] The present embodiment provides a battery B5, wherein the battery cell of the battery B5 includes a stacked battery cell coating film and a polymer base film, and the preparation method thereof is different from that of the embodiment 1 only in that:

[0108] In step (1), the film forming method of the battery cell coating material is different, and the specific steps include:

[0109] Take 80g of polyvinylidene fluoride (PVDF, weight average molecular weight 600,000), dissolve it in 720g of N-methylpyrrolidone (NMP), then add 20g of protoporphyrin IX grafted silicon particles, disperse at high speed for 5h to obtain slurry. Then use PET film with a thickness of 0.1mm as the polymer base film, coat the slurry on one surface of the PET film, dry it at 100℃ and then hot press it to obtain a film with a thickness of 0.11mm, cut the film into the size of the battery cell for use.

[0110] Example 6

[0111] The present application embodiment provides a battery B6, wherein the battery cell of the battery B6 comprises a battery cell coating film, a polymer base film and a battery cell coating film stacked in sequence, and the preparation method thereof is different from that of the embodiment 5 only in that:

[0112] The slurry was coated on two opposite surfaces of the PET film.

[0113] Example 7

[0114] The present application embodiment provides a battery B7, wherein the battery cell of the battery B7 includes a battery cell body and a layer of battery cell coating film coated on the battery cell body. The preparation method thereof is different from that of the embodiment 1 only in that:

[0115] The positive electrode active material in step (2) is lithium nickel cobalt manganese oxide (referred to as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O2).

[0116] Example 8

[0117] The present embodiment provides a battery B8, wherein the battery cell of the battery B8 includes a battery cell body and a layer of battery cell coating film coated on the outside of the battery cell body. The preparation method thereof is different from that of the embodiment 2 only in that:

[0118] The positive electrode active material in step (2) is lithium nickel cobalt manganese oxide (referred to as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O2).

[0119] Example 9

[0120] The present embodiment provides a battery B9, wherein the battery cell of the battery B9 includes a stacked battery cell coating film and a polymer base film, and the preparation method thereof is different from that of the embodiment 3 only in that:

[0121] The positive electrode active material in step (2) is lithium nickel cobalt manganese oxide (referred to as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O2).

[0122] Example 10

[0123] The present application embodiment provides a battery B10, wherein the battery cell of the battery B10 includes a battery cell coating film, a polymer base film and a battery cell coating film stacked in sequence, and the preparation method thereof is different from that of the embodiment 4 only in that:

[0124] The positive electrode active material in step (2) is lithium nickel cobalt manganese oxide (referred to as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O2).

[0125] Embodiment 11

[0126] The present embodiment provides a battery B11, wherein the battery cell of the battery B11 includes a stacked battery cell coating film and a polymer base film, and the preparation method thereof is different from that of the embodiment 5 only in that:

[0127] The positive electrode active material in step (2) is lithium nickel cobalt manganese oxide (referred to as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O2).

[0128] Example 12

[0129] The present embodiment provides a battery B12, wherein the battery cell of the battery B12 includes a battery cell coating film, a polymer base film and a battery cell coating film stacked in sequence, and the preparation method thereof is different from that of the embodiment 6 only in that:

[0130] The positive electrode active material in step (2) is lithium nickel cobalt manganese oxide (referred to as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O2).

[0131] Example 13

[0132] The present embodiment provides a battery B13. The battery cell of the battery B13 includes a battery cell body and a layer of battery cell coating film coated on the battery cell body. The preparation method thereof is different from that of the embodiment 1 only in that:

[0133] In step (2), the positive electrode active material is lithium iron phosphate (LFP for short, chemical formula LiFePO4).

[0134] Embodiment 14

[0135] The present embodiment provides a battery B14, wherein the battery cell of the battery B14 includes a battery cell body and a layer of battery cell coating film coated on the battery cell body. The preparation method thereof is different from that of the embodiment 2 only in that:

[0136] In step (2), the positive electrode active material is lithium iron phosphate (LFP for short, chemical formula LiFePO4).

[0137] Embodiment 15

[0138] The present embodiment provides a battery B15, wherein the battery cell of the battery B15 includes a stacked battery cell coating film and a polymer base film, and the preparation method thereof is different from that of the embodiment 3 only in that:

[0139] In step (2), the positive electrode active material is lithium iron phosphate (LFP for short, chemical formula LiFePO4).

[0140] Example 16

[0141] The present application embodiment provides a battery B16, wherein the battery cell of the battery B16 comprises a battery cell coating film, a polymer base film and a battery cell coating film stacked in sequence, and the preparation method thereof is different from that of the embodiment 4 only in that:

[0142] In step (2), the positive electrode active material is lithium iron phosphate (LFP for short, chemical formula LiFePO4).

[0143] Embodiment 17

[0144] The present application embodiment provides a battery B17, wherein the battery cell of the battery B17 includes a stacked battery cell coating film and a polymer base film, and the preparation method thereof is different from that of the embodiment 5 only in that:

[0145] In step (2), the positive electrode active material is lithium iron phosphate (LFP for short, chemical formula LiFePO4).

[0146] Embodiment 18

[0147] The present application embodiment provides a battery B18, wherein the battery cell of the battery B18 comprises a battery cell coating film, a polymer base film and a battery cell coating film stacked in sequence, and the preparation method thereof is different from that of the embodiment 6 only in that:

[0148] In step (2), the positive electrode active material is lithium iron phosphate (LFP for short, chemical formula LiFePO4).

[0149] Comparative Example 1

[0150] The comparative example of the present application provides a battery R1, the battery cell of the battery R1 includes a polymer base film, and the preparation method thereof is different from that of Example 1 only in that:

[0151] In step (4), a PET film with a thickness of 0.1 mm is directly coated on the outside of the battery cell body.

[0152] Comparative Example 2

[0153] The comparative example of the present application provides a battery R2, the battery cell of which includes a polymer base film, and the preparation method thereof is different from that of Example 7 only in that:

[0154] In step (4), a PET film with a thickness of 0.1 mm is directly coated on the outside of the battery cell body.

[0155] Comparative Example 3

[0156] The comparative example of the present application provides a battery R3, the battery cell of which includes a polymer base film, and the preparation method thereof is different from that of Example 13 only in that:

[0157] In step (4), a PET film with a thickness of 0.1 mm is directly coated on the outside of the battery cell body.

[0158] Comparative Example 4

[0159] The comparative example of the present application provides a battery R4, wherein the battery cell of the battery R4 comprises a battery cell body and a layer of battery cell coating film coated outside the battery cell body, and the preparation method thereof is different from that of Example 1 only in that:

[0160] (1) Preparation of battery cell coating materials

[0161] Take 80g of polyethylene terephthalate (PET, weight-average molecular weight of 100,000) and 20g of protoporphyrin IX, mix them at room temperature for 12h, then make a film by melt spinning at 260°C, and then hot press at 250°C for 1h to obtain a film with a thickness of 0.1mm, and cut the film into the size of the battery cell for use.

[0162] For ease of review, some important preparation conditions of the batteries in Examples 1 to 18 and Comparative Examples 1 to 4 are listed in Table 1 below.

[0163] Partial preparation conditions of the batteries in Examples 1 to 18 and Comparative Examples 1 to 4

[0164]

[0165]

[0166] Test example

[0167] The batteries prepared in the above examples and comparative examples were cycled 1000 times at room temperature and 1C to test the cycle performance, and the content of transition metal ions in the electrolyte after 1000 cycles was measured. The specific test method is as follows:

[0168] 1. Cycle performance test

[0169] The batteries of Examples 1 to 18 and the batteries prepared in Comparative Examples 1 to 4 were tested according to the following steps:

[0170] (1) Leave for 1 minute;

[0171] (2) Discharge from the open circuit voltage to the lower limit voltage with a constant current of 1C;

[0172] (3) Leave for 1 min;

[0173] (4) Charge at a constant current of 1C to the upper voltage limit, and then charge at a constant voltage of 0.05C;

[0174] (5) Leave for 1 min;

[0175] (6) Discharge at a constant current of 1C to the lower limit voltage;

[0176] (7) Leave for 1 min;

[0177] (8) Repeat steps (4) to (7) for 1000 times.

[0178] Among them, the voltage upper limit of Examples 1 to 6 and Comparative Examples 1 and 4 is 4.8V, and the voltage lower limit is 3.5V; the voltage upper limit of Examples 7 to 12 and Comparative Example 2 is 4.3V, and the voltage lower limit is 2.8V; the voltage upper limit of Examples 13 to 18 and Comparative Example 3 is 3.85V, and the voltage lower limit is 2.5V. The test results are shown in Table 2.

[0179] 2. Transition metal ion content test

[0180] The aluminum shell battery after 1000 cycles at 1C at room temperature was disassembled, and 0.5 g of free electrolyte was extracted, and then diluted to 10 g with dimethyl carbonate. The diluted sample was taken and the contents of Fe, Co, Ni, and Mn in the sample were determined by ICP external standard method. The measurement results are shown in Table 3.

[0181] Table 2 Cyclic performance test results of the batteries in Examples 1 to 18 and Comparative Examples 1 to 4

[0182]

[0183]

[0184] Table 3 Transition metal ion content in Examples 1 to 18 and Comparative Examples 1 to 3

[0185]

[0186]

[0187] It can be seen from Table 2 and Table 3 that the batteries prepared in Examples 1 to 18 have a low content of transition metal ions in the electrolyte after 1000 cycles at 1C at room temperature. Correspondingly, the batteries prepared in Examples 1 to 18 have a capacity retention rate of not less than 90% after 1000 cycles at 1C at room temperature, and the capacity retention rate in Example 13 can be as high as 98%, indicating that the battery core coating film can effectively adsorb the transition metal ions dissolved from the positive electrode active material during the cycle, thereby giving it excellent cycle stability.

[0188] Comparing the performance test results of Example 1 and Comparative Example 1, it can be seen that the capacity retention rate of battery B1 is 95%, while in the battery R1 of Comparative Example 1, the content of nickel and manganese ions in the electrolyte increases significantly, and the capacity retention rate decreases significantly to 65%. Comparing the performance test results of Example 7 and Comparative Example 2, it can be seen that the capacity retention rate of battery B7 is 96%, while in the battery R2 of Comparative Example 2, the content of nickel ions, cobalt ions and manganese ions increases significantly, and the corresponding capacity retention rate decreases to 88%. Comparing the performance test results of Example 13 and Comparative Example 3, it can be seen that the capacity retention rate of battery B13 is 98%, while in the battery R3 of Comparative Example 3, the content of iron ions increases, and the corresponding capacity retention rate decreases to 93%. Comparing the performance test results of Example 1 and Comparative Example 4, it can be seen that the capacity retention rate of battery B1 is 95%, while in the battery R4 of Comparative Example 4, the content of nickel and manganese ions in the electrolyte increases, and the corresponding capacity retention rate decreases to 52%.

[0189] The above-mentioned embodiments 1-6 and comparative examples 1 and 4 are batteries of a nickel manganese oxide lithium system, the above-mentioned embodiments 7-12 and comparative example 2 are batteries of a nickel cobalt manganese oxide lithium system, and the above-mentioned embodiments 13-18 and comparative example 3 are batteries of a lithium iron phosphate system. It can be seen from the contents of Tables 2 and 3 that for batteries of different positive electrode active material systems, the technical solution provided in the present application, by arranging a cell coating film including porphyrin compound grafted silicon particles outside the cell body, can efficiently adsorb transition metal ions dissolved from the positive electrode active material during the cycle, and effectively improve the cycle performance during a long cycle, especially effectively improve the cycle stability of the nickel manganese oxide lithium battery system.

[0190] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

Claims

1. A battery core coating film, characterized in that: It includes porphyrin compounds grafted with silicon particles and polymers.

2. The battery core coating film according to claim 1, characterized in that: The thickness of the battery core coating film is 1 nm to 1 mm.

3. The battery core coating film according to claim 1, characterized in that: The mass ratio of the porphyrin compound grafted silicon particles to the polymer is (1-99):(0-99); Optionally, the polymer includes at least one of polyvinylidene fluoride, poly(vinylidene fluoride hexafluoropropylene), polytetrafluoroethylene, polyhexafluoropropylene, polyacrylate, polymethacrylate, polyacrylamide, polymethacrylamide, epoxy resin, polyvinyl pyrrolidone, carboxymethyl cellulose, sodium carboxymethyl cellulose, cellulose or chitosan.

4. The battery core coating film according to claim 1, characterized in that: The battery core coating film further comprises an inorganic oxide, and the mass ratio of the porphyrin compound grafted silicon particles to the inorganic oxide is (1-99):(0-99); Optionally, the inorganic oxide includes at least one of boehmite, alumina, silica, titanium dioxide, ferric oxide or ferrosoferric oxide.

5. The battery core coating film according to claim 1, characterized in that: The battery core coating film comprises a functional layer and a polymer base film, the functional layer comprises the porphyrin compound grafted silicon particles and the polymer, and the functional layer is located on at least one side surface of the polymer base film; Optionally, the polymer base film has a thickness of 1 nm to 100 μm; Optionally, the material of the polymer base film includes at least one of polyethylene terephthalate, polyvinyl alcohol, polyethylene, polypropylene, polyacrylonitrile, polyimide or polyetherimide.

6. A method for preparing a battery core coating film according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: dissolving a porphyrin compound having an alkenyl group in a solvent and mixing the mixture with mercapto-functionalized silicon particles, and performing a grafting reaction under ultraviolet light to prepare the porphyrin compound grafted silicon particles; S2: mixing the porphyrin compound grafted silicon particles and the polymer, and forming a battery core coating film after curing.

7. The method for preparing the battery core coating film according to claim 6, characterized in that: Step S2 includes: The porphyrin compound grafted silicon particles and a polymer are mixed to form a slurry, and the slurry is coated or spun on at least one surface of a polymer base film. After curing, a functional layer is formed on the surface of the polymer base film to obtain the battery core coating film.

8. The method for preparing the battery core coating film according to claim 6, characterized in that: The mercapto-functionalized silicon particles are 3-mercaptopropyl grafted silicon particles; The porphyrin compound having an alkenyl group includes at least one of protoporphyrin, protoporphyrin monomethyl ester, protoporphyrin dimethyl ester, protoporphyrin monosodium salt, protoporphyrin disodium salt, protoporphyrin monolithium salt or protoporphyrin dilithium salt; Optionally, the grafting reaction is carried out at a temperature of 40 to 80° C. and for a time of 6 to 24 hours.

9. A battery cell, characterized in that: It comprises a battery cell body and a battery cell coating film as claimed in any one of claims 1 to 5, wherein the battery cell body comprises a positive electrode sheet, a negative electrode sheet and a separator, the separator is located between the positive electrode sheet and the negative electrode sheet, and the battery cell coating film is coated outside the battery cell body.

10. A battery, characterized in that: It comprises a shell, an electrolyte and a battery cell as claimed in claim 9, wherein the battery cell and the electrolyte are contained in the shell, the electrolyte infiltrates the positive electrode sheet, the negative electrode sheet and the separator, and the battery cell coating film is used to insulate and connect the battery cell body to the shell.

Citation Information

Patent Citations

  • Anode plate and secondary battery

    CN106711400A

  • Battery cell and battery

    CN116345026A